THE CHALLENGES FACED BY ENGLISH STUDENTS IN ACADEMIC WRITING (A CASE STUDY AT UIN SULTHAN THAHA SAIFUDDIN JAMBI) - Sari, Putri Ratna (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This study aimed to investigate the difficulties encountered by students of English in academic writing at the Islamic University State Sulthan Thaha Saifuddin Jambi, focusing on previous academic year 2022/2023. Employing a qualitative approach through a case study design, the research gathered data via interviews and document analysis. Findings revealed that students face several challenges in academic writing, including plagiarism, lexical complexities, grammatical errors, topic selection, inadequate planning, lack of motivation, and punctuation issues.